VC UMPSA speaks at China Conference Heilongjiang - Malaysia Higher Education Week 2024 - Mohd Ferdaus, Musa (UMPSA, 2024)
DAQING, CHINA, 21 April 2024 - The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dato’ Ts. Dr. Yuserrie Zainuddin was invited to deliver a speech at the University President Roundtable Forum in conjunction with the China Conference (Heilongjiang) - Malaysia Higher Education Week 2024 which took place on 19 to 21 April 2024 at Northeast Petroleum University, Daqing recently.